Care Bundles after Discharging Patients with Chronic Obstructive Pulmonary Disease Exacerbation from the Emergency Department - Gómez-Angelats, Elisenda (Med Sci (Basel), 2018)
Chronic obstructive pulmonary disease (COPD) is the second leading cause of emergency department (ED) admissions to hospital, and nearly a third of patients with acute exacerbation (AE) of COPD are re-admitted to hospital within 28 days after discharge. It has been suggested that nearly a third of COPD admissions could be avoided through the implementation of evidence-based care interventions. A COPD discharge bundle is a set of evidence-based practices, aimed at improving patient outcomes after discharge from AE COPD; body of evidence supports the usefulness of discharge care bundles after AE of COPD, although there is a lack of consensus of what interventions should be implemented. On the other hand, the implementation of those interventions also involves different challenges. Important care gaps remain regarding discharge care bundles for patients with acute exacerbation of COPD discharged from EDs There is an urgent need for investigations to guide future implementation of care bundles for those patients discharged from EDs.